Observation of non-locality sharing among three observers with one entangled pair via optimal weak measurement. (December 2018) - Hu, Meng-Jun; Zhou, Zhi-Yuan; Hu, Xiao-Min; Li, Chuan-Feng; Guo, Guang-Can; Zhang, Yong-Sheng
Abstract Bell non-locality plays a fundamental role in quantum theory. Numerous tests of the Bell inequality have been reported as the ground-breaking discovery of the Bell theorem. Up to now, however, most discussions of the Bell scenario have focused on a single pair of entangled particles distributed to only two separated observers. Recently, it has been shown surprisingly that multiple observers can share the non-locality from an entangled pair using the method of weak measurement without post-selection [Phys. Rev. Lett.114, 250401 (2015)]. Here we report an observation of double CHSH-Bell inequality violations for a single pair of entangled photons with strength continuous-tunable optimal weak measurement in a photonic system. Our results shed new light on the interplay between non-locality and quantum measurements and our design of weak measurement protocol may also be significant for important applications such as unbounded randomness certification and quantum steering. Weak measurements: Sharing nonlocality A study shows that the nonlocality of quantum entangled particles can be shared among three observers. Since John Bell's 1964 theorem, which provides experimentally testable inequalities, Bell tests have been used to probe quantum theory. In a typical Bell test scenario, one pair of quantum entangled particles is distributed to two separate observers, usually referred to as Alice and Bob. A team of researchers led by Yong-Sheng Zhang from the University of Science and Technology of China now show that the nonlocality of an entangled pair can be shared with more observers. The team do this by introducing a second Bob to the Bell test, who accesses the same particle from the entangled pair as the first Bob via weak measurements, enabling them to explore the interplay between nonlocality and quantum measurements.